Vestigium strategy for the development of research skills in undergraduate students, Chiclayo 2016 - Castañeda Quiroz, Selfa Obdulia (2017)
This article is the abstract of a research aimed to propose Vestigium Strategy for development of investigative skills in undergraduates of César Vallejo University (UCV). The research was conducted on the basis of the application of the questionnaire instrument to a representative sample of students said top university. The results were analyzed and discussed at the light of recent educational theories on teaching and learning of scientific research, the most important were: i) Insufficient research training in the regular basic education; ii) the vallejian willingness of students to recognize the importance of research in university life; iii) in order of importance, it was identified the limitations of students to conduct research; iv) the ideal researcher profile was determined; v) the strengths and weaknesses of the teaching-learning process in the UCV was identified. The strategy proposal is methodological basis: i) Encourage the development of a profile of vallejian student socially responsible; ii) encourage the development of a profile of vallejian teacher researcher rational, flexible, and respectful interpersonal nature (democratic) to guide the student-researcher not perfectly but innovation; iii) New research development with the latest trends, promoting a style of free inquiry, open and inclusive.